2014
DOI: 10.1590/1809-6891v15i217202
|View full text |Cite
|
Sign up to set email alerts
|

Lesões cutâneas tipo tumorais associadas à infeção por avipoxvirus em uma marreca-cabocla (Dendrocygna autumnalis)

Abstract: O setor de reabilitação de aves selvagens do Parque Mangual das Garças, localizado em Belém, Pará, recebeu um espécime de Marreca-cabocla (Dendrocygna autumnalis). O animal apresentava lesões nodulares em regiões desprovidas de penas na asa, que consistiam de dois grandes nódulos cutâneos de aspecto tumoral, que mediram 4,2 x 3,8 cm e 2,8 x 2,2 cm de comprimento e largura, respectivamente. Os nódulos foram removidos cirurgicamente, fixados em formol a 10%, e as amostras foram processadas para histopatologia, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Although it is not a highly lethal disease and shows an atypical occurrence, avianpox disease is being frequently reported in avian wildlife in Brazil (Catroxo et al 2009, Vargas et al 2011, Pereira et al 2014. In broilers, skin lesions caused by avian poxvirus were detected in carcasses of slaughtered birds from unvaccinated flocks (Fallavena et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not a highly lethal disease and shows an atypical occurrence, avianpox disease is being frequently reported in avian wildlife in Brazil (Catroxo et al 2009, Vargas et al 2011, Pereira et al 2014. In broilers, skin lesions caused by avian poxvirus were detected in carcasses of slaughtered birds from unvaccinated flocks (Fallavena et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This report provides the first molecular characterization of Avipoxvirus detected in tumor-like lesions in avian species. While previous reports have described simultaneous occurrences of SCC or tumor-like lesions and poxvirus detection in lesions in black-bellied whistling duck (Dendrocygna autumnalis) (Pereira et al 2014) and in broilers in Brazil (Fallavena et al. 2002), and pink-backed pelican in Italy (Pesaro et al 2009), there is a lack of molecular characterization of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-like lesions were also reported in the skin of young Chilean flamingos (Arai et al 1991), in the cornea, bursa of Fabricius, in the lungs of Galapagos doves (Mete et al 2001) and canaries (Ritchie & Carter 1995), and head bones of rosy-faced lovebirds (Tsai et al 1997). In Anseriformes, poxvirus infection was reported to be associated (Pereira et al 2014) and not associated (Morton & Dieterich 1979) with cutaneous tumor-like lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2009) reports the presence of Fowlpox in backyard chickens by clinical signs and confirming the diagnosis by histopathology. Vargas et al (2011) reported an infection by Avian poxvirus in barn owl, and Pereira et al (2014) reported a cutaneous tumor-like lesions associated with infection by APV in a Dendrocygna autumnalis. Both studies confirmed the diagnosis by clinical signs as well as by histopathology.…”
Section: Discussionmentioning
confidence: 99%